2014
DOI: 10.1109/tmi.2014.2324900
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Transmural Electrophysiological Imaging Based on Minimization of Total-Variation Functional

Abstract: While tomographic imaging of cardiac structure and kinetics has improved substantially, electrophysiological mapping of the heart is still restricted to the surface with little or no depth information beneath. The progress in reconstructing 3-D action potential from surface voltage data has been hindered by the intrinsic ill-posedness of the problem and the lack of a unique solution in the absence of prior assumptions. In this work, we propose a novel adaption of the total-variation (TV) prior to exploit the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…The third method of the inverse solution, which was designed to complement the second one, is Variational Bayesian Electrophysiological Imaging with a total-variation prior (VB-TV) proposed by Xu et al [23, 24]. The VB-TV method is well suited to extracting cardiac source activity along the MI-scar border in 3D due to the inherent ability of a total-variation prior to extract strongly localized boundaries between homogeneous regions.…”
Section: Methodsmentioning
confidence: 99%
“…The third method of the inverse solution, which was designed to complement the second one, is Variational Bayesian Electrophysiological Imaging with a total-variation prior (VB-TV) proposed by Xu et al [23, 24]. The VB-TV method is well suited to extracting cardiac source activity along the MI-scar border in 3D due to the inherent ability of a total-variation prior to extract strongly localized boundaries between homogeneous regions.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that inverse ECG can be used to detect or quantify myocardial infarcts [1,2]. The main challenge in inverse ECG is the need to solve a severely ill-posed problem.…”
Section: Introductionmentioning
confidence: 99%
“…To address this problem, various regularization techniques have been used in the literature. For the purpose of infarct detection, sparse regularization in the spatial gradient domain of the action potential has been shown to be effective [2]. It is based on the idea that between depolarization and repolarization (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a deterministic setting, spatial and/or temporal smoothness of the source models have been commonly enforced through different numerical techniques such as Tikhonov regularization (zero-order, first-order, and second-order) [25], [22] and truncated SVD [26], [27], [24]. Recently, L 1-norm based sparsity models have also been used to enforce low-dimensional features of the solutions in space [28], [29], [30], [31], [18]. In a probabilistic setting, similarly, Gaussian prior density distributions have been used to enforce the smoothness of the epicardial source distribution [32], [33], [34], [35], [36], [37], [38], while total-variation prior has been recently adopted to preserve the structural sparsity of transmural source distribution [39].…”
Section: Introductionmentioning
confidence: 99%